Analysis of the Factors Influencing Patient Loyalty in the Digital Age: The Role of Service Quality, Patient Experience, and Hospital Reputation: Systematic Literature Review - Christine Dianne Sumarauw; Vip Paramarta; Kosasih Kosasih; Farida Yuliaty (Jurnal Pengabdian Nusantara, 2026)
Patient loyalty is a key indicator of a hospital's management success in maintaining its service ecosystem and competitive advantage. In the digital era, patient loyalty is influenced not only by clinical service quality but also by the patient experience, hospital reputation, and the hospital's ability to provide easy, fast, and responsive digital interactions. This study aims to analyze the factors influencing patient loyalty, focusing on the roles of service quality, patient experience, and hospital reputation through a Systematic Literature Review (SLR) approach. A literature search was conducted on scientific articles published between 2021 and 2026 using relevant databases and journal sources. Articles were selected based on inclusion and exclusion criteria and subsequently analyzed systematically to identify patterns of relationships between variables. The synthesis results indicate that service quality is a fundamental determinant of patient loyalty, as reliable, responsive, safe, and patient-centric care enhances satisfaction and the likelihood of repeat visits. Patient experience is a crucial factor, as loyalty is shaped by the overall experience throughout the patient journey. Hospital reputation also plays a role in building trust and reinforcing patient preferences. Furthermore, digitalization expands patient-hospital interactions through websites, applications, social media, online registration, and telemedicine. The synthesis reveals that satisfaction and trust potentially act as mediators in the relationships between service quality, patient experience, reputation, and loyalty. Consequently, enhancing patient loyalty requires an integrated strategy that combines service quality, patient experience, institutional reputation, digital transformation, satisfaction, and trust.